Plasma lipid profiles and homocysteine levels in anti-N-methyl-D-aspartate receptor encephalitis - Wang, Zhi-hao; Qiao, Shan; Wang, Lei; Wang, Kemo; Zhang, Ranran; Jin, Yang; Wu, Huai-kuan; Liu, Xuewu (Frontiers in Neurology, 2023)
Introduction We aimed to investigate whether lipid profiles and homocysteine levels in patients with anti-N-methyl-D-aspartate receptor encephalitis are related to clinical presentation and prognosis, which may contribute to further research on the pathogenesis and treatment of this disease. Methods This study included a total of 43 patients with anti-N-methyl-D-aspartate receptor encephalitis and 43 sex–age-matched healthy controls. Baseline demography, clinical data, patient outcomes, and ancillary examination results were recorded. Patients were followed up every 2–3 months during the first year. The modified Rankin Scale score was used to evaluate the therapeutic effect and clinical outcome. Results Among the 43 patients included in this study, 55.81% were male, the mean age of onset was 27 years old, and the median modified Rankin Scale score on admission was 3.0. Apolipoprotein A-1 was significantly lower in patients with anti-N-methyl-D-aspartate receptor encephalitis compared with healthy controls (p = 0.004). Compared with healthy controls, homocysteine (p = 0.002), apolipoprotein B (p = 0.004), Lpa (p = 0.045), and apolipoprotein B/apolipoprotein A-1 (p = 0.001) were significantly increased in patients with anti-N-methyl-D-aspartate receptor encephalitis. According to the modified Rankin Scale scores, 6 months after discharge, 72.09% of patients had a good prognosis and 27.91% had a poor prognosis. In the good prognosis group, age (p = 0.031), lipoprotein a (p = 0.023), apolipoprotein A-1 (p = 0.027) at baseline, and the modified Rankin Scale score on admission (p = 0.019) were significantly higher than those in the poor prognosis group. Conclusion This study suggests the possibility that serum lipid profile and homocysteine play an important role in the pathogenesis of anti-N-methyl-D-aspartate receptor encephalitis, providing support for lipid-lowering treatment of anti-N-methyl-D-aspartate receptor encephalitis patients.